2022
DOI: 10.1021/acs.inorgchem.2c01591
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Catalytic Oxygen Reduction Reactions: The Utility of Proton Management Substituents on Cobalt Porphyrins

Abstract: Three ABAB-type cobalt meso-tetraarylporphyrins with fluorine (F-CoPor), acetic acid (AC-CoPor), and cyanoacetic acid (CN-CoPor) groups at the para-positions of phenyl rings at the 10,20-positions are synthesized and evaluated as catalysts for oxygen reduction reactions (ORRs). In density functional theory calculations, the frontier molecular orbitals of these complexes were found to be stabilized relative to model complexes with electron-withdrawing atoms or moieties on the meso-aryl rings. Electrochemical me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…[53] For instance, three ABAB-type cobalt porphyrins with different proton management groups at their peripheral exhibited the limiting current densities 1.5 ~2 times of the magnitude in 0.1 M KOH than in 0.5 M H 2 SO 4 , while their electron transfer numbers showed slightly reduced values in base than in acid. [54] The selectivity towards 4-electron reduction of O 2 , however, often shows poorer in alkali than in acid, which possibly relates to the interfacial charge states, the decreased water activity as well as the restricted proton transfer from water in alkali solution. [48,52] Besides, electron transfer number may change with the angular rate of the RRDE, catalyst thickness, loading and geometry, which should be considered.…”
Section: Orr Mechanisms Of Porphyrin-based Composites In Different El...mentioning
confidence: 99%
See 3 more Smart Citations
“…[53] For instance, three ABAB-type cobalt porphyrins with different proton management groups at their peripheral exhibited the limiting current densities 1.5 ~2 times of the magnitude in 0.1 M KOH than in 0.5 M H 2 SO 4 , while their electron transfer numbers showed slightly reduced values in base than in acid. [54] The selectivity towards 4-electron reduction of O 2 , however, often shows poorer in alkali than in acid, which possibly relates to the interfacial charge states, the decreased water activity as well as the restricted proton transfer from water in alkali solution. [48,52] Besides, electron transfer number may change with the angular rate of the RRDE, catalyst thickness, loading and geometry, which should be considered.…”
Section: Orr Mechanisms Of Porphyrin-based Composites In Different El...mentioning
confidence: 99%
“…The composite catalyst made from compound 55 exhibited the most positive ORR potentials, maximum limiting current density and highest 4-electron selectivity in both acidic and alkaline electrolytes. [54] In many cases of using proton management for altering the electrocatalytic processes, proton-coupled electron transfer (PCET) mechanisms can be adopted for in-depth interpretations. [42,[127][128][129] PCET reactions have been regarded as the engine of energy conversion and storage since their fundamental but importance role in natural and artificial systems.…”
Section: Proton Management Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…4,58 Inspired by CcOs, tremendous efforts have been devoted to tuning the catalytic performance of metal porphyrins through the incorporation of functional groups in the secondcoordination sphere. 28,29,[59][60][61][62][63][64][65][66] For instance, it was demonstrated that introducing hydrogen-bonding interactions, 35,67,68 proton relays 69,70 and electrostatic interactions 71,72 to the molecular backbone of metal porphyrins can dramatically improve the O 2 binding and subsequent conversion to H 2 O. By contrast, metal corrole molecules typically exhibit better catalytic ORR properties than relevant metal porphyrins, 29,31,73 because the trianionic corrole macrocycles are more effective than dianionic porphyrin macrocycles at stabilizing high-valent metal ions, which are intermediates in the ORR process.…”
Section: Introductionmentioning
confidence: 99%